Syndemics, Infodemics, and How the Severity of COVID-19 Was Aggravated by Our Maladapted Lifestyle and by the Political Handling of Public Health - Holly, Jeff M. P. (Frontiers in Public Health, 2021)
The abstract will be disclosed upon article publication